HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN PENGGUNA BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN - Rosiana, Ni Kadek Ita; Rahajeng, Indah Mei; Kamayani, Made Oka Ari (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023, 2023)
The quality of hospital services is a benchmark in assessing the success of a government program. The quality of service that provided by hospital may affects patient satisfaction. Patients using BPJS health insurance often feel dissatisfied with the services received. The measurement of patient satisfaction must be carried out by the hospital as an evaluation material for the quality of services provided, so that later it will have an impact on patient loyalty and hospital profitability. This research aims to identify the correlation of hospital quality of service with patients’ satisfaction among those who hold BPJS health insurance at BRSU Tabanan. The method of this research is quantitative with a cross sectional research design. The sample were 30 respondents selected by quota sampling technique. The service quality questionnaire and HCAHPS questionnaire are used in this research. The results showed that the quality of service reaches an average value of 109,80 and the average value of patient satisfaction of user of BPJS health insurance is 41,13. This study analysis showed that there is a significant moderate relationship between hospital quality of service with patients’ satisfaction (p value 0,001) and with positive direction. The value of the determinant coefficient was 34,2%. The direction of a positive relationship means the better the quality of service the higher the satisfaction of patients using BPJS health insurance, and vice versa.